The legal adoption of unrelated children: a grounded theory approach to the decision-making processes of black South Africans - Gerrand, Priscilla A (My University, 2017)
In South Africa, there are thousands of children who cannot be raised by their parents or relatives and consequently unrelated, legal adoption is usually considered to be in their best interests. South Africa has ratified international agreements, which emphasise that adoptable children have a right to grow up in their country of origin and intercountry adoption should be considered ‘a last resort’. The Children’s Act (No. 38 of 2005) legally entrenches several innovations to facilitate adoptable children being raised in South Africa. Accredited adoption agencies have made ongoing efforts to make adoption more accessible to South Africans, but the number of South Africans legally adopting unrelated children adoption is small and continues to decline. To help address this pressing child welfare problem, the main aim of this research was to develop a grounded theory explaining what factors affect the decision-making processes of urban black South Africans regarding legally adopting unrelated child. This population group was focused on because they presented as a promising pool of prospective adopters. It was reasoned that to facilitate domestic adoption, policy makers and practitioners need to gain a clearer understanding of what factors dissuade black South Africans from legally adopting unrelated children. A qualitative inquiry was conducted using the Corbin and Strauss approach to the grounded theory method. Personal interviews were conducted with 39 purposively selected black participants that were divided into five cohorts, namely i) adopters ii) adoption applicants in the process of being assessed as prospective adopters iii) adoption applicants who did not to enter the assessment process iv) social workers specialising in the field of adoption and v) South African citizens who have some knowledge of legal adoption practice. The grounded theory emerging was ‘Tensions surrounding adoption policy and practice and perceptions and experiences of adoption.’ Essentially this grounded theory is based on five categories: Meanings of Kinship; Information and Support; Cultural and Material Mobility; Parenthood, Gender and Identity and Perceptions of Parenting and Childhood. It is recommended that adoption policy and practice be shaped to reflect a balanced child-centred and adult-centred approach. Furthermore, recruitment strategies should be based on findings at a grassroots level. Key words: legal adoption; adoptable children; Africanisation; decision-making processes, adoption assessment process and grounded theory.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Social Work , Faculty of Humanities, University of Witwatersrand, Johannesburg, 2017
Keywords: Adoption--South Africa; Adopted children--South Africa.; Adoption--Law and legislation--South Africa